Jumping spiders of the tribe Lapsiini Maddison (Salticidae: Spartaeinae) from Colombia: new species and records - Muñoz-Charry, Valentina; Galvis, William; Martínez, Leonel (Zootaxa, 2022)
The spider subfamily Spartaeinae Wanless, with its only New World tribe Lapsiini (Araneae: Salticidae) is for the first time recorded from Colombia. Six new species of the genera Lapsias Simon and Thrandina Maddison are described and illustrated herein from the country. From the Andean region are described: L. iguaque sp. nov. (♂; Boyacá department), Lapsias quimbaya sp. nov. (♂; Quindío, Risaralda, and Caldas departments), L. tequendama sp. nov. (♂; Cundinamarca department), L. walekeru sp. nov. (♂; La Guajira department), and Thrandina colombiaenpaz sp. nov. (♂♀; Huila department). From the Sierra Nevada de Santa Marta, Magdalena department, Caribbean region, is described L. tayrona sp. nov. (♂♀). In addition, new records of Galianora sacha Maddison and L. lorax Maddison for the country are presented, and the female of L. lorax is described for the first time. Finally, a map with plotted distribution of the tribe Lapsiini from South America is presented.